Malignant Proliferating Trichilemmal Tumour of the Deltoid Region in an Adolescent: A Rare Presentation at an Unusual Site and Young Age - Aditya Chadalawada; A Naveen Kumar (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Proliferating Trichilemmal Tumour (PTT) is a rare benign adnexal neoplasm arising from the outer root sheath of the hair follicle. Malignant transformation to Malignant PTT (MPTT) is exceptionally uncommon and is frequently mistaken for squamous cell carcinoma, as the two share overlapping clinical and microscopic features. MPTT classically affects the scalp of women in the sixth-to-seventh decade of life; presentation in adolescence and at an extra-scalp site is rare. The authors report a 16-year-old girl with a painless swelling over the left deltoid region present for one year, with rapid enlargement over the preceding five months. There was no history of trauma or intramuscular injection. An outside incisional biopsy reported MPTT and she was referred for definitive management. Magnetic Resonance Imaging (MRI) showed a 3.1×2.5 cm subcutaneous mass superficial to the deltoid without muscular invasion and a few small left-axillary nodes. After tumour board discussion she underwent wide local excision with 1 cm margins and sentinel lymph node biopsy localised with methylene blue dye; the sentinel node was negative on frozen section and definitive histopathology and all resected margins were free of tumour. Histopathology confirmed MPTT with abrupt keratinisation, nuclear atypia, infiltrative margins and eight mitoses per 10 high-power fields, without lymphovascular invasion. She recovered well, did not require adjuvant radiotherapy and showed no recurrence at follow-up. The present case highlights that MPTT can occur in adolescents and at unusual sites. It must be distinguished from squamous cell carcinoma and complete surgical excision with margin assessment is the cornerstone of management.